The Influence of Ease of Use and Utilization of the E-Stock Application on the Effectiveness of the Learning Process Using the EUCS Method (Case SMKN 10 Samarinda) - Mumek, Trifena Oliviana; Yunita, Y; Yulindawati, Y (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
The management of inventory items in vocational school environments often faces administrative challenges, such as manual record-keeping that is prone to errors and process delays. SMKN 10 Samarinda implemented the E-Stock application as an information system solution to address these issues. This study aims to evaluate user perceptions of the ease of use and utilization of the E-Stock application, as well as its impact on the effectiveness of use in school operational activities and in supporting the efficiency of the learning process, which depends on the availability of facilities and infrastructure. This research employs a descriptive quantitative approach, with data collected through a closed-ended questionnaire distributed to nine active respondents. The instrument consists of 18 statements representing three main variables: ease of use, utilization, and effectiveness. Each item was rated using a Likert scale ranging from 1 to 5. Data were analyzed descriptively using SPSS to obtain the average score for each variable studied. The analysis results show that ease of use received an average score of 4.37, utilization scored 4.40, and effectiveness scored 4.28. All three scores fall into the high category, indicating that users have a very positive perception of the application. Based on these results, it can be concluded that the E-Stock application has met user expectations in supporting work efficiency and school administration, as well as contributing to the smooth running of the learning process through improved inventory management. This study also affirms that evaluation models such as EUCS are relevant to be used in the context of educational information systems.